Analisa Cerobong Asap Gas Hasil Pembakaran Ketel Uap Pada Pabrik CPO - Lelawati lelawati (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2021)
Abstract A steam boiler is a device used to process water into steam with a planned temperature and pressure. Then the steam which has that pressure is flowed into a process. Broadly speaking, the way the boiler works, hot steam that comes out of the fire is absorbed by the boiler wall (heating field). Process of processing palm oil at CPO (Crude Palm Oil) mills Through the process of boiling palm kernels with the help of a much needed tool, namely a steam boiler. A steam boiler is a device that works by heating water to boil and producing hot steam with high pressure, the resulting heat energy or what is often called heat is absorbed by the boiler wall (heating field), then it can be used for boiling coconut ore processes palm.